Application of Petri Net in the planning of a shearing-cut and bending progressive die workstation. (1st January 2001) - Lin, Zone-Ching; Deng, Ching-Hua
The method for analysing the strip workstation of shearing-cut and bending progressive dies is studied. First, the Petri Net model is used to construct the work conditions and synthesizing method of each workstation of the shearing-cut and bending progressive die. The model is able to clearly represent the systems hierarchy and dynamic work conditions such as the upper and lower dies offset displacement during the shearing-cut and bending process and the sheet springback during the process. It is thus capable of planning the work conditions of every workstation of the shearing-cut and bending progressive die. These conditions include: strip message communication through various workstations, the communication of the compensator message for the upper and lower die offset displacement and the communication of sheet springback. The model can distinctively express the design of supporting theories and the planning of information communication during the machining process.